The use of an online learning platform: A step towards e-learning - Mashau, Pfano; Nyawo, Jabulani (South African Journal of Higher Education, 2021)
In South Africa for the last few years, the Higher Education Institutions (HEIs) have experienced unforeseen events that have eventually led to universities’ suspension of academic activities. This has financial implications and leads to the extension of the academic calendar. This article looks at using an online learning platform to respond to unforeseen circumstances and beyond this, a shift to the new mode of university service delivery. The article presents the collective perspective of selected students of the School of Governance at the University of KwaZulu-Natal, South Africa. This quantitative study used a census approach of collecting data from the defined population. A total of 212 questionnaires were distributed to students, of which 107 were completed and returned. E-learning is currently a common topic of conversation and will continue to be so in the wake of the current worldwide COVID-19 pandemic. This study suggests that there is a need to improve students’ experiences of using online learning platforms and doing online assessments to roll out online teaching and learning successfully. The results also suggest that the facilitators need to rethink their teaching pedagogy in the process of shifting to e-learning.